Weathering Characteristics of Wood Plastic Composites Reinforced with Extracted or Delignified Wood Flour - Chen, Yao (Materials (Basel), 2016)
This study investigated weathering performance of an HDPE wood plastic composite reinforced with extracted or delignified wood flour (WF). The wood flour was pre-extracted with three different solvents, toluene/ethanol (TE), acetone/water (AW), and hot water (HW), or sodium chlorite/acetic acid. The spectral properties of the composites before and after artificial weathering under accelerated conditions were characterized by Fourier transform infrared (FTIR) spectroscopy, the surface color parameters were analyzed using colorimetry, and the mechanical properties were determined by a flexural test. Weathering of WPC resulted in a surface lightening and a decrease in wood index (wood/HDPE) and flexural strength. WPCs that were reinforced with delignified wood flour showed higher ΔL(*) and ΔE(*) values, together with lower MOE and MOR retention ratios upon weathering when compared to those with non-extracted control and extracted WF.